Psychosocial interventions for people with dementia: a synthesis of systematic reviews - McDermott, Orii; Charlesworth, Georgina; Hogervorst, Eef; Stoner, Charlotte; Moniz-Cook, Esme; Spector, Aimee; Csipke, Emese; Orrell, Martin (Aging & mental health, 2019)
Objectives: Over the last 10 years there has been a multitude of studies of psychosocial interventions for people with dementia. However, clinical services face a dilemma about which intervention should be introduced into clinical practice because of the inconsistency in some of the findings between different studies and the differences in the study qualities and trustworthiness of evidence. There was a need to provide a comprehensive summary of the best evidence to illustrate what works. Methods: A review of the systematic reviews of psychosocial interventions in dementia published between January 2010 and February 2016 was conducted. Results: Twenty-two reviews (8 physical, 7 cognitive, 1 physical/cognitive and 6 other psychosocial interventions) with a total of 197 unique studies met the inclusion criteria. Both medium to longer-term multi-component exercise of moderate to high intensity, and, group cognitive stimulation consistently show benefits. There is not sufficient evidence to determine whether psychological or social interventions might improve either mood or behaviour due to the heterogeneity of the studies and interventions included in the reviews. Conclusion: There is good evidence that multi-component exercise with sufficient intensity improves global physical and cognitive functions and activities of daily living skills. There is also good evidence that group-based cognitive stimulation improves cognitive functions, social interaction and quality of life. This synthesis also highlights the potential importance of group activities to improve social integration for people with dementia. Future research should investigate longer-term specific outcomes, consider the severity and types of dementia, and investigate mechanisms of change.